The microfinance revolution - Robinson, Marguerite S.; World Bank. (Washington, D.C.: World Bank, 2002)
The book examines many financial institutions, with a special emphasis on Bank Rakyat Indonesia's microbanking system, which in the mid-1980s was transformed from a failed subsidized credit program to a nationwide commercial financial intermediary that now profitably provides microfinance services - savings and credit - to more than 20 million people. Commercial microbanking remained stable and profitable in Indonesia even as the country's financial system collapsed during the recent crisis.
Includes bibliographical references and index.
oif 09/04/14, ijb 26/02/2019
Loans
Keywords: Financial institutions; Poor; Microfinance; Microfinance; Open Society Institute